Environmental Factors Influencing Urban Homicide Clearance Rates: A Spatial Analysis of New York City - Kennedy, Leslie W. (Homicide studies, 2021)
In this paper, we explore the conditions under which clearance rates improve by looking at the experience across New York City. Using one agency provides a control on the administrative differences that appear across other jurisdictions that have been studied, usually through cross-national analysis. Our analysis uses Risk Terrain Modeling (RTM) to identify environmental features that relate to closed versus open homicide cases using two years of New York City Police Department (NYPD) data. This analysis is supplemented with an investigation of precinct-wide social structure variables to examine how context matters in influencing closure rates.